Co-operative agricultural societies in Germany - Finlay, T.A. (Statistical and Social Inquiry Society of Ireland, 1892)
A few days ago Mr. Balfour, in a remarkable speech, announced his conviction that the cure for the evils at present afflicting agricultural industry in these countries, might be found in co-operation. As a preliminary to a discussion of this view, it would be necessary to explain between whom the co-operation is to subsist. Between large landowners and small, or between small landowners amongst themselves, or between landowners and labourers who are not owners of land? Before we can describe a system of co-operation, we must be able to designate the individuals who are to co-operate; and to be able to describe them we must assume as established some system of land tenure, which will determine the condition of the several cooperating parties.
Read Friday, 18th December, 1891
Keywords: Agricultural co-operatives; Germany; 314.15